Satu Keluarga, Satu Komputer (One Home, One Computer): Cultural Accounts of ICTs in South and Southeast Asia. - Bell, Genevieve (Design Issues)
In this article the author examines the impact of information and communication technologies (ICTs) in parts of southern Asia. The author approaches ICTs as a set of social practices rather than merely an array of communication technologies. She employs an intriguing writing strategy to foreground the experiential nature of the design phenomenon under investigation. In conformity to disciplinary models of rigor, she poses a series of questions to be addressed and lays out a methodology for pursuing answers. But she leavens this academic approach with a series of brief intimate isketchesi that evoke the social milieu within which the users of ICTs are embedded.